28/#262 Dose-dense, weekly paclitaxel and carboplatin with or without bevacizumab, in metastatic or recurrent cervical carcinoma (final analysis of JCOG1311). (4th December 2022) - Ishikawa, Mitsuya; Shibata, Taro; Kataoka, Tomoko; Takekuma, Munetaka; Kobayashi, Hiroaki; Yaegashi, Nobuo; Sato, Toyomi
Abstract : Objectives: To assess the efficacy of dose-dense weekly paclitaxel plus carboplatin (ddTC) with or without bevacizumab in metastatic or recurrent cervical carcinoma, we conducted a phase II/III randomized controlled study comparing with conventional TC (cTC) with or without bevacizumab (JCOG1311, jRCTs0311800007). We previously reported that this study had not met the primary endpoint of phase II in ASCO2020. Methods: Patients were randomly assigned to either cTC or ddTC arm The cTC was paclitaxel 175 mg/m 2 and carboplatin (AUC 5) on day 1. The ddTC was paclitaxel 80 mg/m 2 on day 1, 8, 15 and carboplatin (AUC 5) on day 1. Patients on both arms received bevacizumab 15 mg/m 2 if not contraindicated. The primary endpoint of phase II was response rate (RR), and that of phase III was overall survival (OS). Results: A total of 122 patients was enrolled. The RR in ddTC arm was 60.7% and not higher than cTC arm (67.9%). The study was terminated early before starting phase III part. After a further two years of follow-up, the final analysis was conducted. Median OS and progression-free survival (PFS) in cTC arm was 17.7 months and 7.9 months, and in ddTC arm 18.5 months and 7.2 months, respectively. The median follow-up of surviving patients was 2.9 years. There were no significant differences between the arms either for OS or PFS. Adverse events related to bevacizumab in 82 patients included fistula in 5 patients and gastrointestinal perforation in 3 patients. Conclusions: Dose-dense paclitaxel plus carboplatin was not promising for metastatic or recurrent cervical carcinoma.